How well were asthmatic patients educated about their asthma? A study at the emergency department - Lee, P.Y.; Khoo, Ee Ming (SAGE Publications, 2004)
70 patients presented with acute asthma exacerbation requiring nebulised bronchodilator treatment at the emergency department of a teaching hospital in Kuala Lumpur, Malaysia, were interviewed over a two-week period in July 2001. The results snowed that 45 (64) patients had not been educated on the nature of asthma; 30 (43) had not been advised on preventive measures or avoidance of triggers; 54 (77) were not advised about the medications used and their side effects; 42 (60) patients did not know the difference between reliever and preventive medications; 37 (53) were unable to recognize features of worsening asthma and 68 (97) were not told about the danger of non-prescribed self-medication or traditional medications. Only six (9) patients were using peak flow meters and were taught self-management plans. The multiple regression results suggest that patients who were followed up at teaching hospital based clinics were better educated on asthma. In conclusion, asthmatic patients are still not educated well about their disease. Health care providers need to put more emphasis on asthma education so that the number of emergency room visits can be reduced.